Evaluation of SrSc0.175Nb0.025Co0.8O3-δ perovskite as a cathode for proton-conducting solid oxide fuel cells: The possibility of in situ creating protonic conductivity and electrochemical performance - Zhu, A.; Zhang, G.; Wan, T.; Shi, T.; Wang, H.; Wu, M.; Wang, C.; Huang, S.; Guo, Y.; Yu, H.; Shao, Zongping (Pergamon, 2018)
Proton-conducting solid oxide fuel cells (H+-SOFCs) have attracted considerable interest recently. However, the overall cell performance of H+-SOFCs is still low due to the lack of a promising cathode material. In this study, SrSc0.175Nb0.025Co0.8O3-δ (SSNC) was synthesized for evaluation as a cathode material in H+-SOFCs based on a BaZr0.1Ce0.7Y0.2O3-δ (BZCY) electrolyte. The chemical compatibility and stability of the SSNC cathode with the BZCY electrolyte in humidified air were studied. In addition, the electrochemical behavior of the SSNC cathode on the BZCY electrolyte was investigated using SSNC/BZCY/SSNC symmetrical cells at 600 °C in dry air and humidified air at various H2O partial pressures. Promising electrocatalytic activity was observed for the SSNC cathode in humidified air. The area specific resistance obtained on symmetrical cells at 600 °C in a 10% H2O-air atmosphere was 0.26 Ω cm2. A promising peak power density of 498 mW cm−2 was obtained using an anode-supported cell with a 46 μm-thick BZCY electrolyte layer at 700 °C.